A10.21 Toll-Like Receptor Triggering of Human Basophils May Synergise with IgE-Mediated Activation in ACPA+ RA. (25th February 2013) - Suurmond, Jolien; Stoop, Jeroen N; Bakker, Aleida M; Huizinga, Tom WJ; Toes, René EM; Schuerwegh, Annemie JM
Abstract : Background and Objectives: Antibodies against citrullinated proteins (ACPA) are highly specific for rheumatoid arthritis (RA). Recently, we described a cellular immune response against citrullinated antigens that was only present in ACPA+ RA patients. This response was mediated via crosslinking IgE-ACPA bound to basophils, and suggests a major role for FcεRI-positive cells in the pathogenesis of RA. However, other mechanisms could also contribute to basophil activation in RA, for example through endogenous TLR ligands present in synovium, which are thought to contribute to chronicity of RA. As only limited information is present on TLR-expression and function in human basophils, it is not known whether such mechanisms could activate basophils. Therefore we studied the activation of basophils via TLRs in combination with activation via IgE. Because recent studies in mice suggested that Th2-associated immune responses might be protective against arthritis, we also studied the effect of activated basophils on skewing of Th cells. Materials and Methods: Basophils were isolated from healthy donors. Real-time quantitative PCR was used to evaluate RNA expression of TLRs. For TLR-mediated stimulation, basophils were stimulated with pathogen-associated TLR ligands, such as LPS. Activation of basophils was measured using flow cytometry and cytokine assays (multiplex assays and ELISA). Naïve T cells were stimulated in the presence of basophil supernatant to evaluate the effect of TLR- and IgE-mediated activation of basophils on T cell skewing. Results: We show the presence of mRNA for TLR1-8 in human basophils, with transcripts of TLR-4 being most abundant. Basophils responded to TLR triggering with cytokine production, but not with degranulation. Remarkably, simultaneous triggering of basophils via TLR-ligands and IgE greatly enhanced cytokine production. Such synergy in cytokine production by basophils led to great enhancement of Th2 skewing. Conclusions: Our data show that human basophils functionally express TLRs and that the activation via these receptors can synergise with IgE-mediated activation. These findings provide a new perspective on the role of basophils and IgE-ACPA in combination with endogenous TLR ligands as a contributor to Th2 responses in RA patients.